2006
DOI: 10.1080/00365590600744014
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience with ambulatory urodynamics

Abstract: Our results demonstrate that AUM is acceptable and well tolerated by patients with bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…As reported by others 2,3,8,9 urodynamic investigations seemed well tolerated in this study (mean total score = 15.15). .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As reported by others 2,3,8,9 urodynamic investigations seemed well tolerated in this study (mean total score = 15.15). .…”
Section: Discussionsupporting
confidence: 82%
“…Relevant literature and guidelines were also revised by the first author to generate potential items. [1][2][3]8,9 A series of questions, positively or negatively worded, were selected for the development of the scale. A Delphi process was used to gain consensus among the eight persons.…”
Section: Development and Administration Of The Satisfaction Scalementioning
confidence: 99%
See 1 more Smart Citation
“…During AUDS, the patients are not confined to a room and the bladder is filled in a more physiological way, and, therefore, this could help in reproducing patient's symptoms as they are not in a room where the bladder is getting filled with a fluid at a lower temperature with faster speed . Seung‐June et al showed that according to pretest and posttest patient experiences and perceptions that AUDS is a well‐tolerated examination, especially if there is a history of previous urodynamic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in 286 women surveyed, 42.3% were not worried about having the test again, 42.7% said they would reluctantly agree to have the test again, and only 15% stated they would refuse to have the test repeated [6] . Furthermore, patients' pre-test anxiety levels remain low on repeated ambulatory testing [13] .…”
Section: Discussionmentioning
confidence: 99%